O Engajamento do Estudante dos Cursos Técnicos Integrados da EJA-EPT no IFFluminense - Cruz, Saionara Rosa da, Saionara (2025)
Given the persistent challenges faced by Youth and Adult Education (EJA) in Brazil, especially the high dropout rates, this thesis analyzes the engagement of students in Technical Courses Integrated with Professional and Technological Education (EJA-EPT), offered by the Instituto Federal Fluminense (IFF). The research is based on the understanding that engagement is a strategic element both for school retention and for the promotion of significant formative experiences, requiring an approach that considers the multiple factors that permeate the trajectory of subjects in this educational modality. The main objective was to explore and understand the factors that favor the engagement of EJA-EPT students, identifying aspects that contribute to their retention in the courses and subsidizing the formulation of more effective institutional strategies. The theoretical basis articulates the contributions of Bernard Charlot's Theory of Relationship with Knowledge with George Kuh's contributions on student engagement, with an emphasis on the institutional, pedagogical and subjective interactions that shape the academic experience. This is an applied research, with an exploratory design and a qualitative-quantitative approach. Data production involved the application of structured questionnaires (surveys) and semi-structured interviews with students from three IFF campuses, in addition to the analysis of institutional and regulatory documents. Quantitative data were treated using descriptive statistics. Qualitative data were analyzed using Reflective Thematic Analysis, articulated with the Comprehensive Interview Methodology, which enabled an in-depth and contextualized reading of the participants' narratives. The results indicate that student engagement is permeated by structural, institutional and symbolic dimensions. Elements such as institutional support, quality of pedagogical practices, access to student assistance policies, interpersonal relationships and appreciation of students' life trajectories appear as determinants in the construction of bonds with the educational institution and with knowledge. The academic experience is lived in a deeply contextualized way, revealing a dynamic process of negotiation of meanings that goes beyond the school dimension itself. It is concluded that the engagement of EJA-EPT students should be understood as a multidimensional phenomenon, which requires institutions to be sensitive and committed to active listening, recognizing diversity, and developing inclusive educational policies. The research contributes to expanding the debate on school retention and engagement in EJA integrated with Professional Education, reinforcing the importance of humanizing pedagogical practices and the appreciation of subjects' trajectories as the central axis of transformative education.